2016
DOI: 10.15430/jcp.2016.21.4.288
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of p53 Polymorphism at Codon 72 and Association With Breast Cancer in Iran: A Systematic Review and Meta-analysis

Abstract: BackgroundBreast cancer is the most common cancer among women in Iran and the world. Multiple environmental factors and genetic variations such as genetic polymorphisms are of its main causes. p53 gene plays an important role in conserving and sustaining the genome as a tumor suppressing gene. Change and polymorphism at codon 72 of p53 gene are correlated with increased risk of lung, mouth, endometrial, prostate, and colorectal cancers, and could be considered an indicator of susceptibility to breast cancer.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Two separate meta-analyses by Jia et al (36) and Lao et al (37) suggested that the homozygote and heterozygote genotypes of Pro participated in the development of endometriosis in Asian and Caucasian populations. Analysis of this variant among an Iranian population revealed that the Arg genotype increased the risk of breast cancer while Pro served as a protective factor (38). As study limitations, the two population groups were not matched based on age or gender, and there was no evaluation of H. pylori infections, lifestyle or dietary regime.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate meta-analyses by Jia et al (36) and Lao et al (37) suggested that the homozygote and heterozygote genotypes of Pro participated in the development of endometriosis in Asian and Caucasian populations. Analysis of this variant among an Iranian population revealed that the Arg genotype increased the risk of breast cancer while Pro served as a protective factor (38). As study limitations, the two population groups were not matched based on age or gender, and there was no evaluation of H. pylori infections, lifestyle or dietary regime.…”
Section: Discussionmentioning
confidence: 99%
“…The Arg72Pro functional polymorphism of TP53 has been widely assessed in cancer susceptibility studies that have yielded contradictory results. In Iran, investigations on this SNP in primary open angle glaucoma (50) and breast (25) and colorectal (21) cancers have indicated associations with disease risk, but no evidence of association has been identified in gastric (51,52) and head and neck (53) cancer, oral squamous cell carcinoma (54) and also hepatitis C infection (55).…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations may increase cellular expansion, loss of apoptosis and genetic instability (23,24). In this regard, a single nucleotide polymorphism (SNP) on codon 72 of TP53 (rs1042522), which encodes proline (CCC) or arginine (CGC), appears to be associated not only with the risk of certain malignant (e.g., cancers of the breast and gastrointestinal system) (25,26) and chronic diseases (e.g., diabetic nephropathy) (15,27) but also with patient survival and treatment response (28,29 characteristics of these two varieties are distinct, which may influence the ability of the final protein to induce inflammation or apoptosis (30). When considering the role of TP53 in the regulation of cell growth, proliferation and inflammatory processes, previous studies have identified inconclusive results in patients with CAD (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Several risk factors have been explained for BC developing, including genetic background, environmental factors, family history, menstrual and pregnancy status, early menarche, age of menopause, alcohol consumption, and also the previous history of cancer. [4] BC grading and staging play an important role in the prognosis of BC and have been discussed about for many years. Further investigations led to the discovery of human epidermal growth factor receptor-2 (Her-2) marker that acts as an important therapeutic and prognostic factor.…”
mentioning
confidence: 99%